Remote sensing of ecosystem trajectories as a proxy indicator for watershed water balance. Issue 7 (11th June 2018) - Chasmer, L.E.; Devito, K.J.; Hopkinson, C.D.; Petrone, R.M.
Abstract: Ecosystem trajectories are inextricably linked to hydrology; however, water availability is not easily observed within the landscape. The response of vegetation to soil water availability may provide an indicator of local hydrology and the resilience or sensitivity of ecosystems to long‐term changes in water balance. In this study, vegetation trajectories derived from Landsat Modified Soil Adjusted Vegetation Index over a 22‐year period are used as an indicator of spatio‐temporal changes of watershed water balance and surface water storage within 6 proximal watersheds of the Boreal Plains ecozone of Alberta, Canada. The interactions between hydrology, topography, geology, and land cover type are examined as they relate to vegetation change. In this study, we find that run‐off ratio (run‐off/precipitation) is greater within watersheds with greater variability of relief, compared within subhumid, wetland‐dominated watersheds (average = 0.35, 0.20, respectively), which experience lagged run‐off response. A 2‐year drought had a greater impact on vegetation trajectories within variable relief watersheds containing a high proportion of coarse‐grain surficial geology, compared with peatland‐dominated watersheds. The drought extended for an additional 1 to 2 years within 3 subhumid watersheds, reducing watershed run‐off to less than 50 mm per water year (November to October) in 2 watersheds. However, proportional area of decline of Modified Soil Adjusted Vegetation Index was significantly less within these watersheds. The results of this study indicate that wetlands play an important role for local water balance and ecosystem maintenance during periods of water stress and should be considered within land use planning and reclamation strategies of the Boreal Plains.